Politik Agraria dan Ekspansi Perkebunan Sawit di Kawasan Hutan Papua: Studi Kasus Konflik Lahan di Kabupaten Boven Digoel - Kayla Azalia Putri Rasono; Devira Egistin; Andini Nathania Putri; Nurdin; Fullah Jumaynah (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the dynamics of agrarian politics and the expansion of oil palm plantations in forest areas of Papua, with a specific focus on land conflicts in Boven Digoel Regency. The research examines how agrarian regulations, licensing practices, and power relations between the state, corporations, and Indigenous peoples shape social, economic, and ecological outcomes. This study employs a qualitative approach using a literature review method, drawing on academic journals, policy documents, NGO reports, and legal sources relevant to agrarian governance and oil palm development in Papua. Data were analyzed thematically using the frameworks of Political Ecology and Property Rights Theory to understand structural inequalities and overlapping land claims.The findings indicate that oil palm expansion in Boven Digoel has resulted in extensive deforestation, ecological degradation, and the erosion of Indigenous customary land rights. Non-transparent licensing processes, weak enforcement of environmental regulations, and violations of the Free, Prior, and Informed Consent (FPIC) principle have intensified land conflicts between Indigenous communities, the state, and corporations. Economically, the expansion has shifted Indigenous livelihoods from subsistence-based forest management to precarious wage labor, increasing dependency and vulnerability. Socially and culturally, land conversion has disrupted sacred spaces, cultural identity, and collective social structures of Indigenous peoples.